1+y-6y=y-8y+17

Simple and best practice solution for 1+y-6y=y-8y+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+y-6y=y-8y+17 equation:


Simplifying
1 + y + -6y = y + -8y + 17

Combine like terms: y + -6y = -5y
1 + -5y = y + -8y + 17

Reorder the terms:
1 + -5y = 17 + y + -8y

Combine like terms: y + -8y = -7y
1 + -5y = 17 + -7y

Solving
1 + -5y = 17 + -7y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '7y' to each side of the equation.
1 + -5y + 7y = 17 + -7y + 7y

Combine like terms: -5y + 7y = 2y
1 + 2y = 17 + -7y + 7y

Combine like terms: -7y + 7y = 0
1 + 2y = 17 + 0
1 + 2y = 17

Add '-1' to each side of the equation.
1 + -1 + 2y = 17 + -1

Combine like terms: 1 + -1 = 0
0 + 2y = 17 + -1
2y = 17 + -1

Combine like terms: 17 + -1 = 16
2y = 16

Divide each side by '2'.
y = 8

Simplifying
y = 8

See similar equations:

| 4x^2+500x=0 | | -20=2y+2 | | 4e^6x-16e^3x-9=0 | | -7w-6=-4(w-3) | | 9(w-2)=7w-38 | | 9v+32=5(v+8) | | 4(y-9)=-9y-49 | | 3-3*6-3=x | | -6u+18=-3(u+1) | | y^2(y+5)-16(y+5)=0 | | 2y+3y=-15 | | -9x+19x=220 | | 3-3*2+1= | | 4x+2=-12+50 | | 3m-15-5n+mn=0 | | V=BQU | | 1x+1x+10+40=180 | | 90x-15=15(6c) | | 3x-7(4+2)=-x+2 | | 3(4x+1)-2(3x-4)=1 | | p+18=36 | | 3(4h+6)+2(-6h+9)=(h+2) | | x=-3.5+-0.5y | | S=7(3.72)vk+7(3.72)v^2 | | -2=4-3y | | 5.5+4= | | 12x-44-15x=140+80x | | 3x^2+31x-6.1=0 | | 21=9x-33 | | t(-8t^2+16)=0 | | 12x-44-15x=7+4x | | 66x+11=22 |

Equations solver categories